Laboratory Measurements of n >= 3 K-shell Transition Energies of Sulfur Ions from F-like S viii to Li-like S xiv - Rahin, Roi; Hell, Natalie; Beiersdorfer, Peter; Brown, Gregory V.; Cumbee, Renata S.; Kelley, Richard L.; Kilbourne, Caroline A.; Leutenegger, Maurice A.; Porter, F. Scott; Wilms, Jörn (Astrophysical Journal, 2025)
Inner-shell transitions are ubiquitous in nonequilibrium collisionally ionized plasmas, such as supernova remnants, and in photoionized plasmas, such as outflows from active galactic nuclei and X-ray binaries. Inner-shell X-ray emission can help determine key parameters of these systems, such as ionization time, τ, and ionization parameter, ξ. Despite their importance, only theoretical inner-shell transition energies are available for many ions. To provide experimental benchmarks, we have measured the dominant n → 1 K-shell transitions of sulfur ions where n ≥ 3 from Li-like S xiv to F-like S viii using LLNL’s SuperEBIT electron beam ion trap and the NASA/GSFC EBIT Calorimeter Spectrometer (ECS). We identify over 30 spectral features and measure their energies with uncertainties in the ∼0.1-1 eV range. We compare these results to Flexible Atomic Code (FAC) and multireference Møller-Plesset (MR-MP) calculations and find differences between theory and experiment of ∼1 eV for FAC and <0.5 eV for most MR-MP calculations. We also compare these results to two widely used atomic databases, AtomDB and CHIANTI, and find discrepancies as high as 7 eV. Furthermore, many transitions are missing from these databases despite being prominent in our data.
CRIS-Team Scopus Importer:2025-04-01